Current and potential contributions of the Gulf of Lion Fisheries Restricted Area to fisheries sustainability in the NW Mediterranean Sea. (January 2021) - Vilas, Daniel; Coll, Marta; Corrales, Xavier; Steenbeek, Jeroen; Piroddi, Chiara; Macias, Diego; Ligas, Alessandro; Sartor, Paolo; Claudet, Joachim
Abstract: Among FAO's Major Fishing Areas, the Mediterranean and the Black Sea had the highest percentage (62.5%) of stocks fished at unsustainable levels, especially demersal stocks. Spatial-temporal restrictions of fishing activities are important measures used for the management of marine stocks. However, sometimes these regulations are not fully implemented due to a lack of effectiveness and compliance, which contributes to their failure. Here, we developed a food-web model approach using the Ecopath with Ecosim (EwE) model representing the Fisheries Restricted Area (FRA) of the Gulf of Lion ecosystem (CoSEGoL model) prior to the establishment of the fisheries restrictions (2006–2008). We characterized the structure and functioning of the ecosystem before and after its establishment. The constructed food-web model was then fitted to the available time series of data from 2008 to 2016 to verify whether this FRA has contributed to the recovery of target demersal species and the demersal community. The fitted model was used to explore alternative future management scenarios to explore feasible management options in order to ensure a full ecosystem recovery under climate change conditions. Our results suggest a failure in the recovery of target species in the restricted area under the current management scenario, potentially revealing a lack of protection efficiency and/or enforcement. Scenarios of management options under plausible climate futures revealed possible recovery of targeted species, especially European hake. The study highlighted the importance of considering trophic interactions between predators and prey to identify trade-offs and synergies in fisheries management outcomes and the need to consider both fishing and climate dynamics. Highlights: Fishing impacts were higher after the establishment of the Fisheries Restricted Area. Fishing regulations failed to rebuild and protect demersal commercial stocks. The lack of enforcement in the Fisheries Restricted Area contributed to the failure. Alternative management can improve demersal community status in this area. Considering trophic interaction is needed when assessing management options.